ORIENTATION AND PROBLEMATICS OF ARABIC LANGUAGE LEARNING IN THE WORLD OF EDUCATION - Fatimah (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2023)
Learning Arabic Problems are common problems faced by everyone who learns Arabic language, because Arabic is not a language that is easy to master completely due to the many differences between Arabic and Indonesian. The linguistic problems include sound or phonetics, vocabulary, writing, sentence structures are morphology, syntax, semantics. While the problem of non-linguistic include environment, interests and motivation, and methodology. Learning Arabic language for non-Arabs began in the 17th century when Arabic Language began to be taught in England and is growing rapidly in the world to Indonesia at this time. While in America, learning Arabic language only began in 1947.